?????? ?????? ?? ???? ???????? JINAS AND SAJA’ IN SURAT AN-NAZI'AT - Mefta Rahmat Fauzi; Maulana Yusup (Department of Arabic Education of State Collage for Islamic Studies of Mandailing Natal, 2023)
Abstract: Balaghah is one of the great sciences in Arabic, with balaghah science, we can find out how the beauty of words both in terms of pronunciation and in terms of meaning. In the Qur'an there are many extraordinary things or beauty in terms of the science of balaghah, and among them is the beauty of jinas and saja'. The purpose of this study is to find out in which verses there is the beauty of jinas and saja' in surah An-Nazi'at and what types of jinas and saja' are found in surah An-An-Nazi'at. The form of this research is a literature study, namely collecting several books related to this title, and by using a qualitative approach, and this research analyzes the science of balagah about jinas and saja', the analysis of this research is about the corresponding lafazh-lafazh and the same wazan-wazan, and the primary data needed by researchers is Al-Qur'anul Karim and secondary data is books related to balaghah, tafsir and other books. The method used by researchers to collect data is with verses containing jinas and rhymes, then analyzing them with content analysis techniques. The results of this study are that there are 12 verses of jinas, namely jinas Al-Ishtiqaq in verses 2, 3, 4, and 6, and jinas Al-Lahiq in verses 6-7, 7-8, 12-13 and 29-30. while saja' contained in surah An-Nazi'at as many as 28 verses, namely saja' mutawazi in verses 1-5, 6-7, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 28, 29 and 30. And saja' mutharaf in verses 10-14.